Abuso sexual y su influencia en el distanciamiento afectivo hacia el núcleo familiar en paciente femenina de 16 años de edad - Reinoso Francia, Angela Gabriela (2019)
Child sexual abuse is the behavior in which a girl or boy is used, as a sexual object by an elderly person, in terms of age, maturity and power, it is a complex problem resulting from a combination of factors individual, family and social, emotional distancing is one of its consequences mainly due to the inability of the family nucleus to accept that one of its members has been the author of this fact, discharging its anger against the affected one, expelling it from the family nucleus as a solution . The instruments of psychological evaluation, observation guide, clinical history, test of incomplete phrases of Sacks, test of the Family of Luis Font and the post-traumatic stress test of Echeburúa contributed in the diagnosis of the adolescent, the only family group therapies did not have The expected result